Effects of Noise Electrical Stimulation on Proprioception, Force Control, and Corticomuscular Functional Connectivity - Li-Wei Chou; Shiang-Lin Hou; Hui-Min Lee; Felipe Fregni; Alice Yen; Vincent Chen; Shun-Hwa Wei; Chung-Lan Kao (IEEE, 2023)
Sensory afferent inputs play an important role in neuromuscular functions. Subsensory level noise electrical stimulation enhances the sensitivity of peripheral sensory system and improves lower extremity motor function. The current study aimed to investigate the immediate effects of noise electrical stimulation on proprioceptive senses and grip force control, and whether there are associated neural activities in the central nervous system. Fourteen healthy adults participated in 2 experiments on 2 different days. In day 1, participants performed grip force and joint proprioceptive tasks with and without (sham) noise electrical stimulation. In day 2, participants performed grip force steady hold task before and after 30-min noise electrical stimulation. Noise stimulation was applied with surface electrodes secured along the course of the median nerve and proximal to the coronoid fossa EEG power spectrum density of bilateral sensorimotor cortex and coherence between EEG and finger flexor EMG were calculated and compared. Wilcoxon Signed-Rank Tests were used to compare the differences of proprioception, force control, EEG power spectrum density and EEG-EMG coherence between noise electrical stimulation and sham conditions. The significance level (alpha) was set at 0.05. Our study found that noise stimulation with optimal intensity could improve both force and joint proprioceptive senses. Furthermore, individuals with higher gamma coherence showed better force proprioceptive sense improvement with 30-min noise electrical stimulation. These observations indicate the potential clinical benefits of noise stimulation on individuals with impaired proprioceptive senses and the characteristics of individuals who might benefit from noise stimulation.